Circuit level simulation of MRI receive chain using excitation derived from images. Issue 4 (October 2015) - Jouda, Mazin; Gruschke, Oliver G.; Korvink, Jan G.
ABSTRACT: We introduce a novel component‐level simulation method with which to characterize the performance of the electronic interfaces and circuitry of a magnetic resonance imaging (MRI) receiver. The Matlab‐based toolbox first reconstructs idealized coil free induction decay signals from real MR images, then uses these signals to drive a transistor‐level and extracted‐layout simulation of the desired receiver architecture. The simulated receiver's outputs are read back into the toolbox, which then reconstructs the MR images. By comparing the reconstructed images with the original ones, important design characteristics, such as the circuit's noise figure, linearity, phase noise, and inter‐channel coupling, can be investigated in terms of image quality. To validate the method, a new MRI receiver architecture is designed and simulated. The architecture is a 16‐channel multiplexer, designed for a commercially available 0.35 μm CMOS technology, and employs both frequency‐division and time‐division multiplexing to form a combined output signal. The SNR degradation and the circuit's linearity determined from the MR images compare well with the SNR and linearity point predictions from conventional circuit simulations. © 2015 Wiley Periodicals, Inc. Concepts Magn Reson Part B (Magn Reson Engineering) 44B: 102–113, 2015